MENUJU TANAH HARAPAN: KOLONISASI ORANG JAWA DI BENGKULU - . Lindayanti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
The coming of the people from Java to Bengkulu was encouraged by the government policy of colonization and the necessity of labour in the Western enterprises. Besides for controlling and decreasing the population of Java, colonization was also intended to extend and open new agricultural areas outside Java. The new settlers were generally peasant agriculturalists in their original districts. In Bengkulu they struggled to transform jungles and swamps into rice fields. They came in two phases. The first began from 1908 until 1919, and the second was after 1930. Those who came in the first phase were located in Rejang Lebong district around the company and the mining, while those of the second were located in the newly opened locations: Lubuk Mumpo ( Rejang-Lebong), Kemumu and Perbo (Lais). Unfortunately, not all of those new settlers could survive in the new areas. Some left the areas, others stayed with a hope that someday they would possess their own land and therefore would have a better life in the dream land of Bengkulu.